Characterization of working conditions of graduate physiotherapists at the University of Boyacá, Colombia - Castellanos-Vega, Rocío del Pilar; Rodríguez-Navas, Yolvi Amileth (Universidad Pedagógica y Tecnológica de Colombia, 2017)
The objective of this research work was to characterize the socio-demographic conditions and the general aspects of the professional practice of physiotherapy graduates as part of the macroproject called "Working and health conditions of physiotherapists in Colombia". It is a descriptive, cross-sectional study, using a sampling technique of 114 graduates from the Physiotherapy program at THE University of Boyacá, Colombia. The average age was 33.3 years, predominant female sex 95.6%. The most frequent civil status: single 47.4%, while 50% of the interviewee belonged to the social status 3. Regarding the professional aspects; currently 90.4% of physiotherapists are working in jobs related to their profession, 49% of them hold a postgraduate degree; 68% work an average of 8 and 10 hours a day. Despite the working conditions, it is observed that the hours worked, 36.9% of the graduates receive between 2 and 4 minimum Colombian wages. This average salary is comparable to that of other programs such as nursing and healthcare administration, which shows the precarious remuneration of this type of professionals in Colombia.